Induction of COX-2 expression by acrolein in the rat model of hemorrhagic cystitis - Macedo, Francisco Yuri Bulcão (2008)
Aim: Acrolein (ACR) is a urinary metabolite of cyclophosphamide (CPS) and ifosfamide (IFS), which has been demonstrated to be the causative agent of hemorrhagic cystitis (HC), induced by these compounds. In this study, we investigate the participation of cyclooxygenase-2 (COX-2) on ACR-induced HC. Methods: Male Wistar rats (150–200 g; six rats per group) were treated with distilled water or intravesical ACR and analyzed by changes in bladder wet weight, macroscopic and microscopic parameters and COX-2 expression. Results: COX-2 immunohistochemical expression was significant 12 h after ACR administration mainly in subepithelial cells. ACR injection also alters some macroscopic and microscopic parameters in bladder of rats analyzed by Gray’s criteria. Conclusions: COX-2 participates in the pathogenesis of ACR-induced HC first seen 12 h after initial contact between ACR and urothelium.